Mapping Of Costal Abrations in Batang Gasan Sub Distrik in Padang Pariaman Reqency - andriani, Rosi - (STKIP PGRI Sumbar, 2014)
This research aim to analyze and Pemeetaan Abrasion On the Beach District of Batang Gasan Padang Pariaman . ( 1 ) Characteristics Panati ( 2 ) The characteristics of the wave ( 3 ) The rate of sediment transport ( 4 ) Determination of Abrasion Or Balanced on the beach in Batang Gasan District of Padang Pariaman . This type of research is descriptive quantitative . The data source is dat primary and secondary data . Penganmbilan sample of this study conducted by purposive sampling technique , based on the level of abrasion observed and occur along the coast In the District of Batang Gasan as many as three points , namely the study sample Punago Coast , Cape Coast , Coastal Edge labung . The data analysis technique used is the equation for calculating the wavelength , wave velocity , wave energy , the waves high , the rate of sediment transport , and the determinants of abrasion , accretion and balanced .The results of this study describes ( 1 ) characteristic wavy beaches , sheer , very sheer . ( 2 ) The characteristics of the wave can be divided into a) the value of the wavelength , Punago Beach , 62.70 , 102.34 Cape Coast , Coastal Edge labung 99.84 . b ) The value of the wave velocity , 9.89 Punago Coast , Cape Coast 12.54 , Coastal Edge labung 1.06 . c ) The value of the wave energy , beach punago , 0.80 , 1.06 Cape Coast , Coastal Edge labung 1.06 . d ) The high value of the waves , beach Punago , 3.57 , 5.27 Cape Coast , Coastal Edge labung 5.21 . 3 ) The rate of sediment transport , Coastal Punago 2223.67 , 4845.70 Cape Coast , Coastal Edge labung 5374.99 . 4 ) Hasi research and data processing is done in the field and Balanced Abrasion beach experience .